Pengendalian Masalah Kesehatan Mental Remaja melalui Pengenalan Ketrampilan Kecakapan Hidup pada Guru SMP: Controlling Adolescent Mental Health Problems through Introduction of Life Skills to Middle School Teachers - Fatiah Handayani; Zamzaliza Abdul Mulud; Angga Wilandika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Literacy on mental health is an essential agenda for adolescents' personalities. Literacy efforts start by increasing the capacity of youth to develop life skills, and expert teachers facilitate these skills. This Community Service aims to become facilitators of adolescent mental health by introducing mental health and building life. The method activity is training assistance. The training was given to 11 teachers. The training location is at SMP Muhammadiyah 4 Bandung Regency, with the implementation of strict health protocols. Pre-test and post-test questionnaires about mental health and life were given to participants via Google Form. The practicum was carried out using the simulation method. Steps include planning, implementation, and evaluation activities. The pre-test and post-test results showed a significant increase in the knowledge aspect of the participants about mental health and self-awareness and rational thinking p-value of 0.019. Practicum implementation is done by conducting simulations, divided into three groups, each practicing life skill worksheets. Based on the activities that have been carried out, it is necessary to follow up the provision of teachers with the theme of life and expand the sub-themes to form comprehensive knowledge of teachers.